The Influence of Electronic Word-of-Mouth on Online Hotel Booking Purchasing Intention in Online Travel Agent - Adisty, Chiquita Nadzira (Green Publisher Indonesia, 2025)
Electronic Word-of-Mouth (eWOM) has become a critical factor influencing consumer decision-making in the digital tourism industry. In Indonesia, the rapid growth of Online Travel Agents (OTAs) has increased competition, making consumer trust and purchase intentions largely dependent on online reviews. This research aims to analyze the effect of eWOM on online hotel booking purchase intentions, focusing on the credibility, quality, and expertise of reviewers as key determinants of consumer trust and behavior. The study adopts the Information Adoption Model (IAM) and the Theory of Planned Behavior (TPB) as theoretical frameworks to explain how consumers process online information and make booking decisions. A quantitative approach is employed, using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between eWOM dimensions and purchase intentions. PLS-SEM is chosen due to its predictive and exploratory capabilities, allowing comprehensive testing of measurement validity, reliability, and structural path coefficients. Data were collected from OTA users in Indonesia through a structured online survey and analyzed to assess convergent and discriminant validity. The findings reveal that information credibility and reviewer expertise significantly enhance consumer trust, which in turn positively influences purchase intentions. Information quality also plays a mediating role in shaping consumer perceptions. These results suggest that OTAs should prioritize strategies that ensure authentic, high-quality reviews to strengthen customer engagement and conversion rates. This study provides theoretical contributions to eWOM and consumer behavior research while offering practical implications for OTAs to improve digital marketing strategies in Indonesia’s competitive tourism sector.